Perturbative transport experiments on TJ-II Flexible Heliac - Castejón, F.; Ascasíbar, E.; Alejaldre, C.; Alonso, J.; Almoguera, L.; Baciero, A.; Balbín, R.; Blanco, E.; Blaumoser, M.; Botija, J.; Brañas, B.; Cappa, A.; et al. (Вопросы атомной науки и техники, 2002)
Transport properties of TJ-II are explored performing perturbative experiments and taking advantage of TJ-II flexibility. Rotational transform can be varied in a wide range, which allows one to introduce low order rationals and to study their effect on transport. On the other hand, confinement properties can be studied at very different rotational transform values and for different values of magnetic shear: Experiments on influence of the magnetic shear on confinement are reported. In these cases a Ohmic current has been induced in TJ-II plasma to modify magnetic shear and to evaluate itsd effect on confinement, showing that negative shear improves the confinement. Heat transport is also reduced by locating a low order rational near the power deposition profile. Plasma potential profiles have been recently measured in some configurations up to the plasma core with the Heavy Ion Beam Probe (HIBP) diagnostic and the electric field values measured in low-density plasmas are consistent with neoclassical calculations near the plasma core. Plasma edge turbulent transport has been studied in configurations that are marginally stable due to decreased magnetic well. Results show a dynamical coupling between gradients and turbulent transport. Finally, cold pulse propagation has been studied showing ballistic non diffusive propagation.